2018
DOI: 10.3390/polym10010100
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Enhancement of Poly(3-methylthiophene) Nanowires upon Length Variable DNA Hybridization

Abstract: Abstract:The use of low-dimensional inorganic or organic nanomaterials has advantages for DNA and protein recognition due to their sensitivity, accuracy, and physical size matching. In this research, poly(3-methylthiophene) (P3MT) nanowires (NWs) are electrochemically prepared with dopant followed by functionalization with probe DNA (pDNA) sequence through electrostatic interaction. Various lengths of pDNA sequences (10-, 20-and 30-mer) are conjugated to the P3MT NWs respectively followed with hybridization wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…13–15 For example, approaches based on the conformational change of π-conjugated polymers upon DNA hybridization have been developed by numerous scholars. 16–18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13–15 For example, approaches based on the conformational change of π-conjugated polymers upon DNA hybridization have been developed by numerous scholars. 16–18…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] For example, approaches based on the conformational change of p-conjugated polymers upon DNA hybridization have been developed by numerous scholars. [16][17][18] Recently, the hybrid assemblies composed of an organic semiconducting molecule, tri(8-hydroxyquinoline) aluminum (Alq 3 ), and single-strand DNAs (ssDNAs) prepared by Ahn and co-workers were proven to recognize specific tDNA molecules. 19,20 Recently it was found that Schiff base compounds, a class of organic small molecules, exhibit excellent performance in the sensing of metal ions, anions, thiols, nitrogen-containing compounds, pH change, and bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The conformation control and tunable properties afforded by supramolecular materials would be particularly useful for functional materials containing conjugated polymers [10][11][12][13]. Owing to extended π-electron delocalization along their backbones, conjugated polymers exhibit optical properties for applications [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric π-conjugated compounds have been widely explored owing to their novel electrical and optical properties. These fascinating properties allow for various technological applications, such as organic light-emitting diodes (OLEDs), organic field-effect transistors (OFETs), organic photovoltaic cells (OPVCs), electrochromic devices, field emission displays, and actuators [5,6,7,8,9,10,11]. Facile and reliable methods for the detection of biological/chemical substances are important for scientific research due to their substantial application in sensor development.…”
Section: Introductionmentioning
confidence: 99%